(untitled) (Perner’s Contacts, 2018)
The main goal of this article is to determine new way of capacity counting. On the previous research basis it was created the cuboid capacity methodology, which counts timetable convenience value. This value includes chosen parameters and provides the possibility of timetable comparison based on one value, only.